Characterising the educational potentials of mobile applications related to ecology - Maldonado Pérez, María Zoe (2019)
Ten free-download mobile applications (apps) to be used for Ecology teaching and learning have been characterised. The analysis has included not only their technological characteristics but also their ecology content as well as the didactic aspects proposed by such apps. The technological resources studied have shown a high degree of usability, but two-dimensional images with low or null degree of realism have prevailed. Most of the apps have shown a wide variety of contents in their proposal. Few apps included activities for users, and when they did include them, the activities were limited to closed-ended questions or games. In most cases, no assessment activities that would enable meta-reflection were presented. The scientific thinking skills that were mostly promoted were: categorising observations, recognising patterns and thinking about causes and effects. As a result of the systematic analysis of the apps, they can be classified into three large groups: ‘simulations’, ‘gaming apps’ and ‘encyclopaedia apps’ in which different levels of interactivity, multimedia content, breadth, skills involved and cognitive demand prevail.